(untitled) (Revista Latino-Americana de Enfermagem, 2015)
Objective: to analyze the distribution of nursing professionals' workloads, according to the Nursing Intervention Classification (NIC), during the transoperative period at a surgical center specializing in oncology.Methods: this was an observational and descriptive cross-sectional study. The sample consisted of 11 nurses, 25 nursing technicians who performed a variety of roles within the operating room, 16 nursing technicians who worked with the surgical instrumentation and two nursing technicians from patient reception who worked in the surgical center during the transoperative period. An instrument was developed to collect data and the interventions were validated according to NIC taxonomy.Results: a total of 266 activities were identified and mapped into 49 nursing interventions, seven domains and 20 classes of the NIC. The most representative domains were Physiological-Complex (61.68%) and Health System (22.12%), while the most frequent interventions were Surgical Care (30.62%) and Documentation (11.47%), respectively. The productivity of the nursing team reached 95.34%.Conclusions: use of the Nursing Intervention Classification contributes towards the discussion regarding adequate, professional nursing staffing levels, because it shows the distribution of the work load.